Analysis of the Role of Learning Motivation on Student Achievement at Muhammadiyah 32 Elementary School Medan - Lestari, Ari (Universitas Syiah Kuala, 2025)
Learning is a process of human life development. Therefore, effective and integrated learning involves the use of various models or strategies to achieve a goal. In other words, it is the process of acquiring new knowledge, skills, and attitudes, which results in significant changes that are generally permanent. Learning motivation is a form of encouragement that occurs within an individual to carry out tasks within the scope of learning, with goals that have already been instilled or aspired. The parameter used to measure the level of knowledge, mastery of material, and skills of students towards the material provided is learning achievement, typically shown in the form of grades. The purpose of this research is to empirically prove whether there is an influence of self-motivation on student learning achievement. The level of influence of learning motivation significantly affects student achievement simultaneously, while partially, learning motivation has a significant effect on student learning achievement.